The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1097/brs.0000000000001853
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Risk Factors of Cervical Spine Instabilities in Rheumatoid Arthritis

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 45 publications
5
31
0
1
Order By: Relevance
“…Terashima et al . 's research, a prospective over 10‐year cohort study, further demonstrates that long‐term corticosteroid administration is a relatively strong indicator of poor prognosis in RA patients with CSI . This may be explained in that corticosteroid is a double‐edged sword, although it can reduce the disease activity.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Terashima et al . 's research, a prospective over 10‐year cohort study, further demonstrates that long‐term corticosteroid administration is a relatively strong indicator of poor prognosis in RA patients with CSI . This may be explained in that corticosteroid is a double‐edged sword, although it can reduce the disease activity.…”
Section: Discussionmentioning
confidence: 96%
“…One recent prospective study, accomplished by Terashima et al, also showed that established mutilating changes are relatively robust indicators for a poor prognosis of the cervical spine in patients with RA. 37 This will be very instructive to the clinician.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, patients with a worse disease activity score, high disease activity and erosive disease at baseline have a high risk of atlantoaxial involvement in early rheumatoid arthritis (ERA) (disease duration < 12 months) [1]. Affection of the small joints of the hand and foot, failure of antirheumatic therapies, intake of glucocorticoids, young age at diagnosis, level of CRP, female sex, and low BMI were identified as risk factors for cervical involvement [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with RA with confirmed osteopenia or osteoporosis, particularly those with lower BMI appear to be at increased risk of cervical instability [6]. Established mutilating changes, concomitant corticosteroid treatment, and previous joint surgery are relatively robust indicators for a poor prognosis of the cervical spine in patients with RA [7]. Cervical myelopathy manifests itself insidiously, and, once it is established, mortality is a common outcome if the pathology isn't treated [8].…”
mentioning
confidence: 99%